MXene—Conducting Polymer Asymmetric Pseudocapacitors. Issue 7 (20th December 2018) - Boota, Muhammad; Gogotsi, Yury
Abstract: Conducting polymers (CPs) are attractive pseudocapacitive materials which show the highest capacitance under positive potentials in aqueous protic electrolytes. One way to expand their voltage window (thus energy density) in aqueous electrolytes is to manufacture asymmetric supercapacitors using distinctly different anodes. However, CPs lack matching pseudocapacitive anode materials that can perform well in protic electrolytes (e.g., sulfuric acid). 2D titanium carbide (Ti3 C2 Tx ), MXene, as a universal pseudocapacitive anode material for a range of CPs, such as polyaniline, polypyrrole, and poly(3, 4‐ethylenedioxythiophene) deposited on reduced graphene oxide (rGO) sheets, is reported here. All‐pseudocapacitive organic–inorganic asymmetric devices with MXene cathodes and rGO–polymer anodes can operate in voltage windows up to 1.45 V in 3m H2 SO4 . Most importantly, these devices show outstanding cycling performance, outperforming many reported asymmetric pseudocapacitors. Abstract : The manufacturing of all‐pseudocapacitive asymmetric supercapacitors composed of MXene as a negative and conducting polymer as a positive electrode results in high energy and long cycle life devices is described.